Pengaruh penambahan EM4 dan gula merah terhadap kualitas gizi Sslase rumput gajah (Pennesetum purpereum). - Herlinae Herlinae; Yemima Yemima; Hanggulan Harat (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The purpose of the study is to know the effect of adding EM4 and palm sugar on the nutrition quality of elephant grass (Pennisetum purpereum) silage and also to know the interaction effect between EM4 and palm sugar. This research used factorial 2 x 2 with complete random experimental design, A Factor (EM4) with level (A0 : A1) and B Factor (palm Sugar) with level (B0 : B1). Observation was conducted through laboratorium test for proximate analysis (Protein content, Crude Fiber, Fat) and pH. This research shown that the usage of EM4 and palm sugar has effect on the quality of elephant grass silage, mean while interaction between the usage of EM4 and palm sugar have not a real effect. Key words : Silage, elephant grass, Pennisetum purpereum, EM4, palm sugar